Correlations for roughness, slope and peak height for bead blasted surfaces. (2nd April 2016) - Wahid, S. M. S.; Madhusudana, C. V.
Abstract : Surface texture plays an important role in understanding heat flow through the interface of the contacting surfaces. In a majority of experimental investigations, however, only the surface roughness is reported. Hence, it was found desirable to determine functional relationship between the rms roughness, slope and peak heights. This work reports the results of measurements of the topography of 79 rough surfaces. The materials were stainless steel, mild steel, aluminium and copper. The surfaces of the specimens were blasted with particles of different materials at a range of pressures. It was found that profile heights were generally Gaussian. Simple correlations between measured parameters were developed. Analysis was also conducted based on the effect of different cut-off lengths. It was confirmed that roughness parameters are not intrinsic properties of the surface, but depend on the cut-off length.